THE EXPERIMENTAL REASON OF THE AUTHOR'S PROGRAMME OF THE DEVELOPMENT AND IMPROVEMENT OF IMAGES OF THE MOTIVE STUDENTS AWF OF FIRST NEAR THE TEACHING OF GYMNASTIC PRACTICES. - Zdzieszynski A.; Skowron J.; Niznikowski T.; Boloban W. (Kharkov National Pedagogical University, 2010)
The low level of the quality of the teaching of gymnastic practices was affirmed on practical occupations from gymnastics at students AWF. It was established on the basis of conducted investigations and experts opinion that the insufficient development was one of causes at the students of motive images about made gymnastic practices. The author's programme of the development was created and the improvement of the motive images which was introduced on practical occupations near the teaching of gymnastic practices. Author's programme turns on four programmes of practices. They have aims, tasks, centres, the elements of control and control and adequate names to their aims: "The time of the movement", "The sense of the movement", "Spatial orientation", "The control of the pose of the body". Introduced author's programme differentiated the efficiency of teaching and the realization of gymnastic practices on the advantage of the experimental group on the end of the experiment indeed (p < 0,05).